2018
DOI: 10.1021/acs.nanolett.8b01649
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Enhanced Charge-Density Wave Order of Monolayer VSe2

Abstract: How the interacting electronic states and phases of layered transition-metal dichalcogenides evolve when thinned to the single-layer limit is a key open question in the study of two-dimensional materials. Here, we use angle-resolved photoemission to investigate the electronic structure of monolayer VSe grown on bilayer graphene/SiC. While the global electronic structure is similar to that of bulk VSe, we show that, for the monolayer, pronounced energy gaps develop over the entire Fermi surface with decreasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
254
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(292 citation statements)
references
References 48 publications
(107 reference statements)
32
254
6
Order By: Relevance
“…In some cases, the monolayer of these materials may exhibit new properties compared to their bulk counterpart, for example, ferromagnetic ordering has been observed in monolayer VSe 2 while the bulk is paramagnetic to low temperatures . Moreover the CDW order temperature may be different for mono‐ and few‐layer samples compared to that of the bulk …”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the monolayer of these materials may exhibit new properties compared to their bulk counterpart, for example, ferromagnetic ordering has been observed in monolayer VSe 2 while the bulk is paramagnetic to low temperatures . Moreover the CDW order temperature may be different for mono‐ and few‐layer samples compared to that of the bulk …”
Section: Introductionmentioning
confidence: 99%
“…Several scanning tunneling microscopy (STM) (Figure B) and angle‐resolved photoemission (ARPES) studies (Figure C) have consistently confirmed the CDW order in MBE‐grown monolayer VSe 2 . The main controversy is however centered around its intrinsic magnetic state.…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 78%
“…B, Atomic resolution STM image of monolayer VSe 2 . C, ARPES intensity map of monolayer VSe 2 in comparison with theoretical spin‐resolved and nonmagnetic electronic bands . D, In‐plane magnetic hysteresis of monolayer VSe 2 grown on MoS 2 substrate .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
See 2 more Smart Citations